Patogenitas Isolat Jamur Entomopatogenik Metarhizium anisopliae terhadap Lalat Rumah Musca domestica L. (Diptera: Muscidae) - Kustiati, Noni Yunizar Rahmawati (Jurnal Protobiont, 2018)
Metarhizium anisopliae is one of the entomopathogenic fungi that can be used to control house fly, Musca domestica. The aim of this study is to determine the effectiveness of fungus Metarhizium anisopliae in killing house flies. This study used a Completely Randomized Design (CRD) with 5 treatment concentration of Metarhizium anisopliae fungal suspension concentration of 1x106 conidia/mL, 3x106 conidia/mL, 5x106 conidia/mL, 7x106 conidia/mL, 9x106 conidia/mL with each repetition three times. The fungal pathogenicity was determined by the lethal time of 50% flies (LT50) for each concentration using Probit analysis. The result of this study showed that the time required to killing 50% of flies in consecutive consentrations was 7 days with concentrations ranging from 3x106 conidia/mL until 5x106 conidia/mL. In conclusion, the fungus Metarhizium anisopliae is effectively deadly pest house flies Musca domestica.